The Impact of Promotion, Quality of Goods, and Consumer Satisfaction on the Purchase of spare parts at PT. Oto Rezeki Indonesia - Kelvin; Fenny Krisna Marpaung; Andini Alfin; Anjani Alfin; Juli Meliza (International Journal Of Economics Social And Technology, 2023)
This study aims to determine the effect of Promotion Level, Quality Goods and Satisfaction Consumer To Purchase Goods at PT Oto Rezeki Indonesia. This research uses the type of quantitative data and the population in this study are whole consumers in 2021 amounted to 523 by sample study a total of 83 samples were counted use formula slovin. Research results in a manner Partial showing that Promotion Level own influence to Purchase Goods by having mark t count (4.684) > t table (1.99006) with level significant 0.000 <0.05, Quality Goods own influence to Purchase Goods by having mark t count (2.768) > t table (1.99006) with a level significant 0.007 <0.05, Satisfaction Consumer own influence to Purchase Goods by having mark t count (2.329) > t table (1.99006) with level significant 0.022 <0.05 and Promotion Level, Quality Goods and Satisfaction Consumer influential and significant to Purchase Goods at PT Oto Rezeki Indonesia by owning F count (25.303) > F table (2.72) with a significance of 0.000 <0.05